Genomic Copy Number Variations in the Autism Clinic—Work in Progress - Velinov, Milen (Frontiers in Cellular Neuroscience, 2019)
The development of advanced technology for microarray-based chromosomal studies helped discover increased prevalence of genomic copy number variants (CNVs) in individuals with autism spectrum disorder (ASD). Chromosomal microarray analysis (CMA) is now an important tool for clinical investigations in patients with ASD. While this technology helps identify high proportion of CNV positive individuals among patients with autism, the clinical interpretation of such genomic rearrangements is often challenged by inconsistent genotype-phenotype correlations. Possible explanations of such inconsistencies may involve complex interactions of potentially pathogenic CNV with additional (secondary) CNVs or single nucleotide variants (SNVs). Other involved factors may include gender-specific effects or environmental contributions. Development of risk models for interpreting such complex interactions may be necessary in order to provide better informed genetic counseling to the affected families.